Clinical Characteristics and Prognosis of 218 Patients With COVID-19: A Retrospective Study Based on Clinical Classification - Yan, Xiquan; Han, Xiaotong; Peng, Danhong; Fan, Yong; Fang, Zhixiong; Long, Da; Xie, Yu; Zhu, Shuibo; Chen, Fang; Lin, Wei; Zhu, Yimin (Frontiers in Medicine, 2020)
Background: Coronavirus disease 2019 (COVID-19) is an emerging infectious disease that has spread worldwide. Methods: This was a retrospective case series involving 218 patients admitted to three tertiary hospitals in the Loudi, Shaoyang, and Xiangtan areas of China from January 21 to June 27, 2020, who were confirmed by RT-PCR to have SARS-CoV-2 infection. The patients’ clinical characteristics, laboratory results, treatments, and prognoses based on clinical classification were recorded. Poor outcome was defined as admission to an ICU, the use of mechanical ventilation, or death. Results: The patients were classified into four clinical groups based on disease severity, namely mild (10/218, 5%), moderate (146/218, 67%), severe (24/218, 11%), or critical (14/218, 6%), and 24 (11%) asymptomatic cases were also included in the study. The most common symptoms were self-reported cough (162/218, 74%), fever (145/218, 67%), sputum production (99/218, 45%), and fatigue (77/218, 35%). Among the 218 patients, 192 (88%) received lopinavir/ritonavir and interferon-alpha inhalation, and 196 (90%) patients received traditional Chinese medicine. Among the severe and critical patients, 25 (11%) were admitted to ICU with or without mechanical ventilation, and one patient died. The presence of diabetes (relative risk [RR], 3.0; 95% CI, 1.3–6.8; p = 0.007) or other comorbidities (RR, 5.9; 95% CI, 1.9–17.8; p = 0.002) was independently associated with poor outcome. To date, 20 (9%) patients have retested positive for SARS‐CoV‐2 RNA after recovering and being discharged. Conclusion: The majority of patients in this case series were clinically classified as having moderate COVID-19. Older patients tended to present with greater levels of clinical severity. The prognosis for patients who were elderly or had diabetes or other chronic comorbidities was relatively poor.